‘I’d Give My Right Arm to Be Ambidextrous’: Exploration Unit Managers Facing Competing Demands for Differentiation and Integration - Cylien Gibert; Sihem BenMahmoud-Jouini (M@n@gement)
This paper examines how managers of internal exploration units – also labeled as innovation labs – address the competing demands of differentiation and integration over time, and the implications for their unit’s ability to execute its intended exploration strategy. Based on a longitudinal study of four exploration units implemented by established firms, we find that their managers face two types of undocumented paradoxical tensions: one related to the evolution of the mandated charter and the other related to the implementation of the performance management system. In response, we show that exploration unit managers adopt four balancing patterns to face these paradoxical tensions: decoupling, conforming, promoting, and synchronizing. These patterns consist of specific combinations of differentiating and/or integrating practices. Drawing on paradox research, we show how each pattern facilitates or impedes the pursuit of the unit’s intended exploration strategy. Our research contributes to the development of a more integrative and systemic understanding of the locus of structural ambidexterity and how it is pursued in practice, and to current debates about the different types of responses adopted when faced with paradoxes. Finally, we provide managerial insights into the management of exploration units and innovation labs within established firms.